2023
DOI: 10.1111/1750-3841.16524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactic acid bacteria fermentation on the physicochemical and structural characteristics of starch in blends of glutinous and japonica rice

Abstract: In this study, the effects of lactic acid bacteria (LAB) fermentation on the physicochemical and structural characteristics of mixed starches in blends of glutinous and japonica rice were investigated. Five starter cultures improved in varying degrees the hydration ability, transparency, and freeze-thaw stability of the mixed starches. Mixed starch I, prepared by fermentation of Lactobacillus acidophilus HSP001, exhibited optimal water-holding capacity, solubility, and swelling power. In comparison, mixed star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Bian et al found that the fermentation of lactic acid bacteria reduced the solubility of glutinous rice starch, increased the swelling potential, and decreased the gelatinization viscosity and thermal properties. 2 Furthermore, Wang et al 3 reported that fermentation with different lactic acid bacteria could improve the hydration capacity and gelatinization properties of rice starch (PV increased, setback (SB) and Δ H decreased), increased storage modulus ( G ′) and loss modulus ( G ′′) possibly because fermentation resulted in enhanced entanglement and interaction between starch molecules, forming a more powerful gel network structure. After lactic acid bacteria fermentation, the gelatinization temperature of sorghum starch decreased, peak viscosity (PV) increased, and in vitro digestibility of starch increased.…”
Section: Introductionmentioning
confidence: 99%
“…Bian et al found that the fermentation of lactic acid bacteria reduced the solubility of glutinous rice starch, increased the swelling potential, and decreased the gelatinization viscosity and thermal properties. 2 Furthermore, Wang et al 3 reported that fermentation with different lactic acid bacteria could improve the hydration capacity and gelatinization properties of rice starch (PV increased, setback (SB) and Δ H decreased), increased storage modulus ( G ′) and loss modulus ( G ′′) possibly because fermentation resulted in enhanced entanglement and interaction between starch molecules, forming a more powerful gel network structure. After lactic acid bacteria fermentation, the gelatinization temperature of sorghum starch decreased, peak viscosity (PV) increased, and in vitro digestibility of starch increased.…”
Section: Introductionmentioning
confidence: 99%
“…Rice has been the main source of carbohydrates in Asian cultures for thousands of years, and over time, its cultivation and production have expanded around the world [2]. According to [3] carbohydrates are nutrients that provide energy for the body, and in some societies, rice is a staple food that accounts for the majority of daily energy intake.Rice produces water from soaking the rice before the cooking process, known as rice washing water [4], [5]. Rice-washing water is included in household waste because it is a by-product that is not used anymore and has not been managed for human needs [6].…”
Section: Introductionmentioning
confidence: 99%